2022
DOI: 10.3390/jpm12081213
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association of Universal Screening and Treatment for Major Depressive Disorder with Survival in Cancer Patients

Abstract: Evidence for clinical screening and intervention for depression in cancer and the effect of this intervention on cancer prognosis is suboptimal. This study substantialized a complete model with universal screening and intervention for major depressive disorder (MDD) and explored its effect on survival in patients. This longitudinal study recruited cancer patients routinely screened for MDD with a two-stage model. Data including sex, age, cancer diagnosis, first diagnosis date, date of death, cancer stage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…They can be significant barriers to management and control, adherence to the treatments, length of stay at the hospital, and ultimately survival rate ( 21 , 22 ). Preceding studies on epidemiology reported that patients with cancer are more likely to experience depressive and anxiety disorders than the general population ( 19 , 20 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…They can be significant barriers to management and control, adherence to the treatments, length of stay at the hospital, and ultimately survival rate ( 21 , 22 ). Preceding studies on epidemiology reported that patients with cancer are more likely to experience depressive and anxiety disorders than the general population ( 19 , 20 , 23 ).…”
Section: Introductionmentioning
confidence: 99%